Inventory of Medicinal Plants Used Traditionally to Manage Kidney Diseases in North-Eastern Morocco: Ethnobotanical Fieldwork and Pharmacological Evidence - Noureddine Bencheikh; Amine Elbouzidi; Loubna Kharchoufa; Hayat Ouassou; Ilyass Alami Merrouni; Hamza Mechchate; Imane Es-safi; Christophe Hano; Mohamed Addi; Mohamed Bouhrim; Bruno Eto; Mostafa Elachouri (Plants, 2021)
Kidney disease is one of the most common health problems and kidney failure can be fatal. It is one of the health disorders associated with extreme pain and discomfort in patients. In developing countries, such as Morocco where socioeconomic and sanitary conditions are precarious, medicinal plants are considered the primary source of medication. In the present work an ethnobotanical survey was conducted in a remote area of North-Eastern Morocco and we focused on (1) establishing a record of medicinal plants used traditionally by local people to treat kidney diseases and (2) correlate the obtained ethnomedical use with well-studied pharmacological evidence. From February 2018 to January2020, information was gathered from 488 informants using semi-structured questionnaires. The data were analyzed using three quantitative indices: The use value (UV), family use value (FUV), and informant consensus factor (ICF). A total of 121 plant species belonging to 57 botanical families were identified to treat kidney diseases. The families most represented were Asteraceae (14 species), followed by Lamiaceae (12 species) and Apiaceae (10 species). The most commonly used plant parts were leaves, followed by the whole plant and they were most commonly prepared by decoction and infusion. The highest value of the (UV) index was attributed to Herniaria hirsuta L. (UV = 0.16), and the highest family use value (FUV) was assigned to Caryophyllaceae with (FUV = 0.163). Regarding the informant consensus factor (ICF), this index’s highest values were recorded for kidney stones (ICF = 0.72). The use of 45% of the selected plants were validated based on literature review. This study helped document and preserve crucial traditional plant knowledge of 121 plant species used to treat kidney problems that can be used in the search for new biologically active compounds through more upcoming pharmacological studies.